RAHASIA POINT OF VIEW KISAH-KISAH DALAM AL-QUR’AN: TELAAH INTRINSIK SASTRA DAN ILTIFĀT - Rahmawan, Hatib (Al Hikmah, 2023)
The stories in the Qur'an possess a unique nature that distinguishes them from general literary works. However, both general literature and the Qur'an share common structural elements, one of which is the point of view. Until now, this element has rarely been employed to analyze the literary aspects of the Qur'an. On the other hand, within the field of Balaghah (rhetoric), there is a topic closely related to the point of view, known as the style of iltifāt. In its discussion, iltifāt often examines the meaning of shifts in perspective, such as the change from the third person (ghaib) to the first person (mutakallim), and so on. These two fields intersect, making them ideal for a synergistic approach, particularly in analyzing the stories in the Qur'an. So, how is the point of view in Qur'anic stories when viewed from both literary and Balaghah perspectives, specifically through the lens of iltifāt? Furthermore, what meanings arise from these two analyses? This study aims to answer these two questions: First, to describe the forms of point of view in Qur'anic stories from both literary and iltifāt perspectives; Second, to explain the meanings and insights derived from these two perspectives. The study's main findings are as follows: First, the point of view in Qur'anic stories holds uniqueness and superiority over common literary narratives; Second, the point of view strengthens the Qur'an's literary miracle and refutes the claim that the Qur'anic language is merely a reproduction of the Prophet's speech; Third, the point of view effectively portrays a strong depiction of God's character; Fourth, the point of view helps explain the communication model and the impression conveyed by the stories in the Qur'an. Keywords: Narrator, Point of View, and Iltifāt.